2011
DOI: 10.1007/s00167-010-1384-x
|View full text |Cite
|
Sign up to set email alerts
|

Intra-articular variations of the long head of the biceps tendon

Abstract: The prevalence of embryological variations of the biceps tendon may be higher than common presumptions, and a particular type of these variants displays an increased association with labral pathologies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 23 publications
(27 reference statements)
0
21
0
Order By: Relevance
“…Several anatomic variations of the intra-articular part of the LHBT exist, and some types seem to be associated to labral pathologies [10, 11]. Anatomic variations have been described concerning the origin of the tendon with more than 50% being from the posterior labrum but with unknown clinical relevance [12].…”
Section: Anatomymentioning
confidence: 99%
“…Several anatomic variations of the intra-articular part of the LHBT exist, and some types seem to be associated to labral pathologies [10, 11]. Anatomic variations have been described concerning the origin of the tendon with more than 50% being from the posterior labrum but with unknown clinical relevance [12].…”
Section: Anatomymentioning
confidence: 99%
“…In one study variant intra-articular LHBT anatomy was present in 1.91 % of a retrospective review of 2,976 shoulder arthroscopies [1]. A separate review of 671 shoulder arthroscopies showed a higher prevalence of intra-articular LHBT variant anatomy of 7.4 % [2]. Classification systems for variant intra-articular LHBT anatomy have been proposed [1].…”
Section: Discussionmentioning
confidence: 99%
“…The LHBT may also originate from the rotator cuff, have an extra-articular origin, or be congenitally absent [4][5][6]. Clinically, there is an association between variant intraarticular LHBT anatomy and other shoulder pathologies, especially labral tears [1,2]. US has been shown to be both sensitive and specific in the detection of LHBT full thickness tears and subluxation and dislocation [7].…”
Section: Discussionmentioning
confidence: 99%
“…Frank et al found that an age of less than twenty years and participation in sports as an overhead thrower increased the risk of revision surgery after the repair of a SLAP tear 44 . These findings, in addition to the presence of a coexisting rotator cuff tear, have negative prognostic indications for patients undergoing operative repair of a SLAP tear [45][46][47][48] .…”
Section: Slap Tears and The Biceps Tendon In Throwing Athletesmentioning
confidence: 99%